PENERAPAN MEDIA ”PAHADAK” PAPAN KOTAK HAK DAN KEWAJIBAN UNTUK MENINGKATKAN PEMAHAMAN SISWA SEKOLAH DASAR KELAS IV MATERI PPKn SD Negeri 065853 Medan - Morita Br Manurung; Ismail Saleh Nasution (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The aim of this research is to increase students' understanding of SDN 065853 Medan in the PPKn Education area, especially in the area of ​​Rights and Obligations at Home and at School. This research involves the use of the media "Pahadak" Box Board of Rights and Obligations. This research uses the PTK (group practice learning) method which includes two different stages: cycle 1 and cycle II. Data collection techniques used in this research include observation, documentation and evaluation. The subjects of this research were all students at SD 065853 Medan, namely 19 students consisting of 14 male students and 5 female students. Based on this research, it shows that the use of the "Pahadak" method of the Rights and Obligations Box Board helps improve elementary school students' understanding of the National School 065853 Medan in Civics subjects. Based on the results of the presentation in the initial cycle, 47% of the 9 students succeeded in understanding the material. There was an increase of 16 students in cycle II or 84%. It can be concluded that the majority of students really understand the content of using the "Pahadak" method of the Rights and Obligations Box Board in the National School Civics Education subject 065853 Medan, in the 2024/2025 academic year.